Severity of Postcovid Syndrome: A Systematic Review - A. A. Karaseva; A. D. Khudiakova; E. V. Garbuzova; Yu. I. Ragino; I. I. Logvinenko (Архивъ внутренней медицины)
Postcovid syndrome includes many conditions and symptoms, both those that arose directly during the acute period of infection and the appearance of new ones. The purpose of the systematic review is to determine the criteria for the severity of postcovid syndrome. Materials and methods. The following keywords were used to search for literary sources: “postcovid syndrome”, “severity of postcovid syndrome”, “severity of postcovid syndrome” and “symptoms of postcovid syndrome” in Russian and English. We used the search engines “eLibrary.RU — Scientific Electronic Library” and PubMed.gov. Articles were included that presented a study of patients with laboratory-confirmed coronavirus infection at least a month after recovery from COVID-19 with residual clinical signs and/or biochemical changes. The analysis included only publications from the last 3 years (2020– 2023). Results. A total of 2,913 publications were found by two search engines. After removing duplicates, literature reviews, clinical studies of medicines, studies conducted on animals, studies unsatisfactory for time after acute COVID-19, and studies performed on persons under the age of 18, 69 articles were selected for analysis that meet the criteria for inclusion in the analysis. Conclusion. An analysis of the literature of the last 3 years has allowed us to determine that the presence and severity of postcovid syndrome can probably be determined by the presence in a patient of at least one of the signs presented in the review that developed during or after a laboratory-verified COVID-19 infection and persisted for more than 4 weeks from the onset of the disease and that cannot be explained by other reasons.